Trend of ABO and Rh Blood Group among the Students of Community Based Medical College Bangladesh - Begum, Nilufar; Haque, Amdadul; Tumpa, Fatema Akhter (Community Based Medical Journal, 2017)
This cross sectional study was done at department of Transfusion Medicine in Community Based Medical College (CBMCB) to know the Prevalence of ABO blood group and Rh group systems among the students selected for admission into CBMCB. Sample size was 555. Male female ratio was 67:33 with mean age was ±19 years. Maintaining aseptic precaution blood samples were collected by venepuncture with disposable syringe without anticoagulant. Antigen-antibody agglutination test was done in slide method for ABO and Rh(D) blood grouping by mixing individual blood sample with Anti A, Anti -B, Anti-D human antisera. Results were taken by visually and under microscope in low power. Blood group differs person to person due to genetically determined antigen. This study showed highest frequency of blood group B (33.5%) followed by O (32.5 %), A (23.37%) and AB (10.63%) in ABO system and In Rhesus system, frequency of Rh-positive was 97.12% and Rh-negative was 2.88%. Results were comparable with different foreign studies. Fair blood grouping assist the safe blood transfusion and reduce the morbidity and mortality considerably. CBMJ 2017 July: Vol. 06 No. 02 P: 12-14